Status quo of implementation of advance care planning: a review - Liu Min; Dela Rosa Ronnell D. (Sciendo, 2022)
Optimum care for patients with a terminal illness is dependent on understanding their values, beliefs, and preferences on end-of-life issues and providing service that meets their preferences. As the only way to explore patients' living wills, advance care planning (ACP) is an important means to honor patient autonomy and respect their human rights and dignity. ACP has been recognized as a key indicator for quality palliative care and endorsed into national health systems by many high-income countries; however, it is little known in mainland China. China is now facing a growing aging and terminally ill population with many unmet needs for end-of-life care; therefore, it is imperative to implement ACP in China. In this review, we clarify the relevant concept and suitable population for ACP, describe the current situation of implementation in high-income countries, and provide better suggestions for the future development of ACP in the mainland of China.